2017
DOI: 10.1016/j.cbpa.2016.08.020
|View full text |Cite
|
Sign up to set email alerts
|

The expression of nuclear and membrane estrogen receptors in the European eel throughout spermatogenesis

Abstract: Estradiol (E) can bind to nuclear estrogen receptors (ESR) or membrane estrogen receptors (GPER). While mammals possess two nuclear ESRs and one membrane GPER, the European eel, like most other teleosts, has three nuclear ESRs and two membrane GPERs, as the result of a teleost specific genome duplication. In the current study, the expression of the three nuclear ESRs (ESR1, ESR2a and ESR2b) and the two membrane GPERs (GPERa and GPERb) in the brain-pituitary-gonad (BPG) axis of the European eel was measured, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 62 publications
4
17
0
Order By: Relevance
“…the proliferation of gonocyte and spermatogonia, spermiation, sperm transport, and epididymal sperm maturation [26]. In eels, estrogen receptors are also expressed in the testis and are required for spermatogonial renewal [27,28]. The high expression of estrogen receptors suggest that estrogen signals are also needed for spermatogenesis in grouper.…”
Section: Discussionmentioning
confidence: 99%
“…the proliferation of gonocyte and spermatogonia, spermiation, sperm transport, and epididymal sperm maturation [26]. In eels, estrogen receptors are also expressed in the testis and are required for spermatogonial renewal [27,28]. The high expression of estrogen receptors suggest that estrogen signals are also needed for spermatogenesis in grouper.…”
Section: Discussionmentioning
confidence: 99%
“…Although speculative, this could indicate a weakening of dopamine-mediated neuroendocrine inhibition of eel puberty. The pituitary is a major target for estrogen in European eel (Morini et al 2017b). In our data, esr1 expression increased significantly in the pituitary after the T10 treatment (Fig.…”
Section: Differential Brain and Pituitary Gene Expressionsupporting
confidence: 66%
“…Furthermore, higher plasma androgen levels have been correlated with European eel SPGA proliferation in previous studies (Peñaranda et al 2016). As mentioned above, increases in steroid levels have been reported in European eel after salinity acclimation (Morini et al 2017b;Peñaranda et al 2016;Baeza et al 2014); however, the duration of these increases has not been reported.…”
Section: Functional Annotationmentioning
confidence: 89%
See 2 more Smart Citations